Uterine-Artery Embolization or Myomectomy for Uterine Fibroids. Issue 12 (December 2020) - Manyonda, Isaac; Belli, Anna-Maria; Lumsden, Mary-Ann; Moss, Jonathan; McKinnon, William; Middleton, Lee J.; Cheed, Versha; Wu, Olivia; Sirkeci, Fusun; Daniels, Jane P.; McPherson, Klim
Abstract : (Abstracted from N Engl J Med 2020;383:440–451) The most common type of tumor among women of reproductive age is uterine fibroids. The prevalence of these tumors increases with age.